Mourning and Intermittence between Proust and Barthes - Rushworth, J (Edinburgh University Press, 2016)
This essay explores the relationship between mourning and writing by tracing the various uses and connotations of the term ‘intermittence’ in the writings of Marcel Proust and Roland Barthes, with particular reference to the middle volume of A la recherche du temps perdu, Sodome et Gomorrhe, and to Barthes’s posthumously published Journal de deuil. Against the backdrop of the Proustian ‘Intermittences of the Heart’, I demonstrate that intermittence is a useful interpretive framework for Barthes’s Journal in terms of the sporadic rhythm of the author’s experience of grief, and suggest that this rhythm is audible in and performed by the Journal’s fragmented, discontinuous form. Finally, intermittence in its etymological meaning of ‘sending between’ is brought to bear on broader, fundamental questions concerning the purpose of mournful writing, including to whom it is addressed and of what it speaks.